Quality of life and cost-effectiveness of combined therapy for reflux esophagitis - 姒健敏 王良静 陈淑洁 赵岚 戴宁 (Journal of Zhejiang University. A. Science, 2003)
Objective : To evaluate clinical, Quality of Life (QoL) and medical cost outcomes in patients with symptomatic reflux esophagitis (RE) receiving different "triple combination therapy". Methods: A muhicenter medical effectiveness trial conducted in 10 hospitals of 5 regions in Zhejiang Province. 248 patient-volunteers were assigned to 8 weeks of " triple combination therapy" with Lansoprazole plus Cisapride and Sucralfate or Ranitidine plus Cisapride and Sucralfate. Main outcomes assessment included symptoms scale scores, RE severity, QoL at baseline and 8 weeks. Medical cost data were collected with cost analysis questionnaire. Resuits: (1)More Lansoprazole group patients noted RE symptoms resolution than Ranitidine group(92.3 % vs 78.4%, P < 0.01). There was no striking difference between two groups in RE healing rate (90.8% vs 82.9% , P > 0.05) . (2)RE significantly impaired QoL of patients( P < 0.001 ). Compared with Ranitidine group, QoL in Lansoprazole group had significant improvement ( rate of "good" QoL 64.5 % vs 45.6 %, P <0.01 ). (3)There was close correlation between symptomic effectiveness and QoL rating scale in both the Lansoprazole and Ranitidine group( P < 0.01, r = 0.235 and 0.353 respectively) . There were no statistical difference of medical cost between the two groups ( P > 0.05 ) . Conclusion : RE significantly impaired QoL of patients. "Triple combination therapies" can significantly improve RE symptoms and QoL. Lansoprazole combination therapy was more cost-effective than Ranitidine combination group.